Distribution, relative abundance, and developmental morphology of paralarval cephalopods in the western North Atlantic Ocean - Vecchione, Michael; Roper, Clyde F. E.; Sweeney, M. J.; Lu, C. C. (2001)
NH-Invertebrate Zoology NMNH NH-SMS